Management Accounting in the Age of AI: Data Transformation, Efficiency, and Modern Decision-Making - Manggu, Sri Astuty Ratnasari (ProBisnis : Jurnal Manajemen, 2023)
The development of artificial intelligence (AI) technology has brought significant changes in management accounting practices. AI not only speeds up the data processing process, but it also improves the accuracy of the information used in planning, control, and decision-making. This article aims to analyze how the integration of AI in management accounting can improve operational efficiency and provide a competitive advantage for organizations in the digital age. The method employed is a literature study, examining the latest research results and modern organizational practices that have adopted AI technology. The findings demonstrate that AI facilitates automated budgeting, data-driven predictive analysis, cost anomaly detection, and enhanced transparency in managerial reporting. However, the application of AI still faces obstacles in the form of a lack of competent human resources, technology investment costs, and data security risks. This article emphasizes the significance of strategic collaboration between technology and accounting in creating a flexible, efficient, and sustainable management system